T. S. Eliot in context - Harding, Jason (Cambridge, UK ; New York : Cambridge University Press, 2011)
"T. S. Eliot's work demands much from his readers. The more the reader knows about his allusions and range of cultural reference, the more rewarding his poems, essays and plays are. This book is carefully designed to provide an authoritative and coherent examination of those contexts essential to the fullest understanding of his challenging and controversial body of work. It explores a broad range of subjects relating to Eliot's life and career; key literary, intellectual, social and historical contexts; as well as the critical reception of his oeuvre. Taken together, these chapters sharpen critical appreciation of Eliot's writings and present a comprehensive, composite portrait of one of the twentieth century's pre-eminent men of letters. Drawing on original research, T. S. Eliot in Context is a timely contribution to an exciting reassessment of Eliot's life and works, and will provide a valuable resource for scholars, teachers, students and general readers"--
Machine generated contents note: Introduction Jason Harding; Part I. Life: 1. St Louis Earl K. Holt III; 2. New England Eric Sigg; 3. Paris William Marx; 4. London C. D. Blanton; 5. Englishness Simon Grimble; 6. The idea of Europe Jeroen Vanheste; Part II. Forms: 7. The role of the intellectual Michael Levenson; 8. Publishing Jason Harding; 9. Censorship Rachel Potter; 10. Literary journalism Peter White; 11. Visual art Charles Altieri; 12. Dance Terri Mester; 13. Drama Richard Badenhausen; 14. Music David Fuller; 15. Radio Michael Coyle; Part III. Literary Cross-Currents: 16. Allusion Hugh Haughton; 17. Classics Hannah Sullivan; 18. Dante Massimo Bacigalupo; 19. Seventeenth-century literature Jennifer Formichelli; 20. Romantic and Victorian poetry Michael O'Neill; 21. French poetry Stephen Romer; 22. Georgian poetry Peter Howarth; 23. Bloomsbury Mark Hussey; 24. Ezra Pound Anne Stillman; 25. The avant-garde Marjorie Perloff; Part IV. Politics, Society and Culture: 26. Politics David Bradshaw; 27. Economics Adam Trexler; 28. Anti-Semitism John Xiros Cooper; 29. Gender Rachel Blau DuPlessis; 30. Religion Barry Spurr; 31. Philosophy Manju Jain; 32. Social science Jewel Spears Brooker; 33. Natural science Michael H. Whitworth; Part V. Reception: 34. Contemporary reviews Martin Dodsworth; 35. Contemporary and postwar poetry Stephen Regan; 36. Eliot studies Benjamin G. Lockerd; 37. Legacies: from literary criticism to literary theory Patricia Waugh; Guide to further reading; Index.
Bibliografija: str. 395-406. - Kazalo
Keywords: Eliot, T. S. -- 1888-1965 -- Criticism and interpretation; Eliot, Thomas Stearns